Evaluation of the Plastic Surgery In-Service Training Exam: Lower Extremity Questions - Silvestre, Jason; Basta, Marten N.; Serletti, Joseph M.; Chang, Benjamin (Journal of surgical education, 2015)
To facilitate the training of plastic surgery residents, we analyzed a knowledge-based curriculum for plastic and reconstructive surgery of the lower extremity. The Plastic Surgery In-Service Training Exam (PSITE) is a commonly used tool to assess medical knowledge in plastic surgery. We reviewed the lower extremity content on 6 consecutive score keys (2008-2013). Questions were classified by taxonomy, anatomy, and subject. Answer references were quantified by source and relative year of publication. Totally, 107 questions related to the lower extremity (9.1% of all questions) and 14 questions had an associated image (13.1%). Questions required decision making (49%) over interpretation (36%) and direct recall (15%) skills (p < 0.001). Conditions of the leg (42.1%) and thigh (24.3%) constituted most of the questions. Subject matter focused on flap reconstruction (38.3%), nerve injury (8.4%), and congenital deformity (6.5%). Analysis of 263 citations to 66 unique journals showed that Plastic and Reconstructive Surgery (54.9%) was the highest yield primary source. The median year of publication relative to PSITE administration was 6 (range: 1-58) with a mode of 2 years. Plastic Surgery by Mathes et al. was the most referenced textbook (21.9%). These data establish a benchmark for lower extremity training during plastic surgery residency. Study efforts focused on the most common topics and references will enhance trainee preparation for lower extremity PSITE questions.